Association of Coping Strategies and Medication Adherence: A Systematic Review - Avinash Chatoo; SuHak Lee (University of Minnesota Libraries Publishing, 2022)
Background: Medication adherence is difficult for most patients who take at least one medication. Poor drug adherence is a developing problem since it contributes to negative outcomes, prescription waste, increased healthcare expenses, and disease progression. Coping strategies are an important tool for managing a patient's condition because a patient's coping method influences how he or she perceives the situation and deals with the stress that comes with it, which can eventually affect adherence. Coping strategies are classified into five categories: problem-focused, emotion-focused, seeking understanding, support seeking, and problem avoidance. Objective: The goal of this study is to examine and illustrate the association of coping strategies on medication adherence. Method: A systematic review of PubMed/MEDLINE database was conducted in order to screen and select articles. A total of 15 studies were included where they were classified by endpoints. Endpoints that were considered are medication adherence, problem-solving/active coping strategy, emotion-focused coping strategy, seeking understanding coping strategy, support seeking coping strategy and problem avoidance coping strategy. The association of each coping strategy on medication adherence was then evaluated from each article assigned to every category of coping strategies to determine if it had a favorable, negative, or no impact on medication adherence. Results: Most studies which measured problem-solving/active coping strategy (78%) had a positive association on medication adherence, followed by studies which measured emotion-focused coping strategy (69%). Majority of the studies that evaluated for problem avoidance coping strategy (50%) showed a negative association on medication adherence and a small proportion of studies (30%) showed a positive association. Four(4) of the 5 coping strategies (problem-solving/active, emotion-focused, seeking understanding and support seeking) were found to have a greater number of studies showing positive association to medication adherence as opposed to problem avoidance. Conclusion: The findings may suggest that problem-solving and emotion-focused coping strategies can be useful to help people with chronic conditions improve their medication adherence. More study is needed to establish a link between coping strategies and medication adherence in patients, which will allow pharmacists and other healthcare professionals to deliver better interventions to patients and assess for medication nonadherence due to poor coping skills.